2012
DOI: 10.1262/jrd.2012-034
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Androgen Receptor, Estrogen Receptors Alpha and Beta and Aromatase in the Fetal, Perinatal, Prepubertal and Adult Testes of the South American Plains Vizcacha, <i>Lagostomus maximus</i> (Mammalia, Rodentia)

Abstract: Abstract. Androgens and androgen receptor play a critical role in spermatogenesis and fertility in mammals, and estrogens and their receptors contribute to regulation of testicular function through initiation and maintenance of spermatogenesis and germ cell division and survival. However, results from different species are still far from establishing a clear understanding of these receptors in the different cell types from the testis. We analyzed the expression of androgen receptor, estrogen receptors α and β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Thus, the Leydig cells can synthesize estrogen and androgen. This result is similar to that of previous studies on other animals such as South American plains vizcachas [18], sika deer [21, 22], humans [7, 8, 26], stallions [13], rams [6], boars [16] and shiba goat [49]. Many previous studies identified localization of this enzyme in other testicular cells, such as Sertoli cells and/or germ cells, in raccoons [39], wild ground squirrels [32], Japanese black bears [38], Japanese raccoon dogs [43], Hokkaido brown bears [44], American black bears [45], northern fur seals [46], mice [37] and rats [30].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the Leydig cells can synthesize estrogen and androgen. This result is similar to that of previous studies on other animals such as South American plains vizcachas [18], sika deer [21, 22], humans [7, 8, 26], stallions [13], rams [6], boars [16] and shiba goat [49]. Many previous studies identified localization of this enzyme in other testicular cells, such as Sertoli cells and/or germ cells, in raccoons [39], wild ground squirrels [32], Japanese black bears [38], Japanese raccoon dogs [43], Hokkaido brown bears [44], American black bears [45], northern fur seals [46], mice [37] and rats [30].…”
Section: Discussionsupporting
confidence: 93%
“…In the boar, ERα was localized in spermatogonia and primary spermatocytes, whereas ERβ immunoreactivity was localized in Sertoli cells. 39 , 40 In the South American Plains Vizcacha fetal and prepubertal testes, 16 ERα and ERβ were expressed in seminiferous tubules and the interstitium, respectively. Yet in adult testes, both ERα and ERβ co-localized in Leydig and peritubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of ERs in testicular cells is not only species-specific but also varies depending on the type of receptor and the developmental stage of the germ cell. 16 In most species analyzed, such as human, rat, cat and dog, ERα and ERβ co-localize in spermatogonia, spermatocytes and spermatids as well as in Sertoli, Leydig, and peritubular myoid cells and these locations appeared to change with age in some reports. 17 , 18 In other species, such as the boar, ERα and ERβ localize separately to spermatogonia/primary spermatocytes and Sertoli cells, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Its concentration was quantified by absorption at 260nm Table 2. These primers were previously employed in vizcacha (Gonzalez et al 2012, Charif et al 2016. Quantitative measures were performed using a Stratagene MPX500 cycler (Stratagene, California, USA).…”
Section: Rna Isolation and Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%